A conceptual model for the chemo-mechanical degradation of granular geomaterials. Issue 3 (3rd September 2012) - Buscarnera, G.
Abstract : A conceptual model is presented, the main aim of which is to elucidate the microscopic origins of the chemo-mechanical coupling in granular geomaterials. The study focuses on the interplay between the inelastic response under high compressive stresses and the chemical reactions leading to mineral dissolution. Chemical and mechanical processes are incorporated within a thermodynamic framework in which energy storage mechanisms depend on microstructural properties. Coupling between the two processes is reproduced through a simplified microscopic idealisation that establishes a link between the evolving microstructure (i.e. particle size geometry) and a chemical state variable. The mechanical implications at the continuum scale are finally derived through statistical homogenisation. The results disclose a relation between the evolution of the elastic properties of a chemically weathered geomaterial and the yielding threshold under high compressive stresses. Such dependency is obtained as an emergent property by advocating that the main contribution to the mechanical dissipation derives from the brittle breakage of the mineral compounds. This result stresses the importance of identifying the key physical processes that regulate macroscopic inelastic phenomena and can constitute a conceptual springboard for the development of chemo-mechanical models.